Complex environmental indexes of city systems - Приходько, В. Ю. (Man and Environment. Issues of Neoecology, 2014)
Methodological principles of city’s complex environmental indexes determination of are presented from positions of intrasystem and external connections. Their determination is conducted on the basis of numerical score of environmental characteristics taking into account weight each of them in the composition a complex index. The values of complex indexes allow to estimate favorableness of conditions and level of human pressure.